Foreign Language Anxiety in English Speaking Activities: A Mixed-Methods Study of Rural Indonesian School Students - Florentinus Sugandi; Lusi Nurhayati; Yuyun Yulia (Journal of Innovation and Research in Primary Education, 2026)
Foreign language anxiety significantly impedes English learning, particularly in under-resourced rural schools where students face limited exposure and inadequate learning resources. This study examined the nature and sources of English learning anxiety among junior high school students in a remote Indonesian school. An explanatory sequential mixed-methods design was employed with 36 eighth and ninth-grade students. Quantitative data were collected using the State-Trait Anxiety Inventory (STAI) to measure anxiety levels, while qualitative data from semi-structured interviews with 18 high-anxiety students and two teachers, combined with classroom observations, explored anxiety sources. The mean State Anxiety score of 69.5 indicated moderately high to high anxiety levels, particularly during speaking activities. Strong negative correlations emerged between anxiety and self-confidence (r = -0.866, p < 0.001). Thematic analysis identified three primary anxiety sources: fear of negative peer evaluation, insufficient preparation time, and perceived low ability relative to classmates. Both state and trait anxiety significantly impeded students' English engagement across contexts. Findings support Krashen's Affective Filter Hypothesis while extending it by demonstrating how both state and trait anxiety dimensions contribute to emotional barriers in language acquisition. Contextual factors specific to rural, under-resourced settings amplified anxiety beyond levels observed in advantaged environments. Results suggest anxiety reduction requires supportive classroom atmospheres, cooperative learning with adequate preparation, and explicit peer norms prohibiting ridicule.